Effect of crystal orientation on microstructure and properties of bulk Fe2B intermetallic. Issue 2 (28th January 2015) - Ma, Shengqiang; Huang, Zhifu; Xing, Jiandong; Liu, Guangzhu; He, Yaling; Fu, Hanguang; Wang, Yong; Li, Yefei; Yi, Dawei
Abstract: Abstract : The effects of Fe2 B-grain orientation on microstructure and properties of bulk Fe2 B intermetallic fabricated by directional and ordinary solidification techniques have been investigated. The results show that unidirectional solidified Fe2 B intermetallic possesses a strong (002) texture in the transverse direction owing to the opposite unidirectional heat-squeeze effect while random Fe2 B grains can be produced under ordinary solidification conditions. The nonoriented Fe2 B intermetallic has the highest linear expansion coefficient of 13.04 × 10 −6 °C −1 while the microhardness and fracture toughness of transverse Fe2 B intermetallic in the (002) plane are larger than those of Fe2 B with other grain orientations and their values are ∼18.72 GPa and 6.42 MPa·m 1/2, respectively. Liquid zinc corrosion results indicate that unidirectional Fe2 B intermetallic with long axis perpendicular to the direction of liquid zinc corrosion displays the best corrosion resistance to liquid zinc owing to its beneficial barrier effect. The FeB transition phase can naturally form and grow parabolically during liquid zinc corrosion.